Upaya Penguatan Kapasitas Ekonomi Cambodia, Laos, Myanmar, Vietnam (CLMV) Melalui Initiative for Asean Integration (IAI) - Sudewi, Ida Ayu Manik; Sushanti, Sukma; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT Following the enlargement process inlate 1990 decade, diversity in ASEAN increased. ASEAN also divided into old and new members which then evoke a development gap between ASEAN-6 and CLMV. This gap is both an obstacle and a challenge for ASEAN to achieve a common goal as a regional organization. The IAI was initiated as an effort to address these challenges with the ASEAN-6 framework helping CLMV. This research analyzes how ASEAN's efforts as a regional organization in increasing the economy capacity of CLMV countries. This research used qualitative methods with secondary data sources. Then the secondary data were analyzed with the concept of functional regional organization and functionalism. The results of this research show that the IAI framework spreads the benefits or spillover effects of functionalism that affect various sectors in the CLMV countries, thus moving the economies of the four countries to narrow the development gap in ASEAN. Keywords: ASEAN, Initiative for ASEAN Integration (IAI), ASEAN-6, CLMV